Handling Interservice Time Constraints in Wireless Networks - Xu Zheng; Jianzhong Li; Hong Gao (International Journal of Distributed Sensor Networks, 2015)
Cyber physical systems collect plenty of information from physical world. This information must be transmitted to the base station immediately to support the making of controlling orders since the physical world keeps transforming rapidly. Such a fact needs the support of real-time transmitting in CPS. Real-time traffic often has some extra QoS requirements. For example, regulating the interservice time, which is the time between two consecutive transmissions of a link, is essential for the real-time traffic in wireless networks. A guarantee of the interservice time of a single user is a precondition to support the normal operating of a system. As far as we know, none of previous work can guarantee the performance on the interservice time. Motivated by this, we design a framework for interservice time guaranteed scheduling. We first define a new capacity region of networks with a strict interservice time guarantee. It is an extension of the well-accepted definition on basic capacity region. Then we propose a novel scheduling policy that is both throughput-optimal and interservice time guaranteed. Simulation results show the policy performs well in interservice time and throughput.